Reinforced concrete building design project & project based learning - Abdul Aliy, Muhammad Yusuf Mohamed Ismail (2019)
Manual calculation was used to determined suitable size of critical structural member size only. This method is not really economical since only one size is applied throughout all related structural members. As an example, if a beam only loaded with minimum load, a critical size of beam will be applied. It is very complicated for an engineer to calculate on each particular beam. Therefore, esteem software was introduced. This is to ease the engineers work and produce more economical and might be cheaper value of particular project. There are few differences were determined after finished with both manual calculation and esteem result of our RC Design Project. All the differences were affected by few reasons. One of the reasons is in manual calculation. only critical structural members were calculated. While in esteem, the calculations and result were shown precisely through each structural members. This is to helps in produce more economical value of a particular project. Which is only increase the structural members size that are failed. Moreover, all the data such as permanent and variable action were inserted separately depends on the particular member. Other than that. at a first place, the structural drawing were draw manually and simply assign few unnecessary structural members especially column. However, whenever running the Esteem to obtain the results, it showed that few columns are not needed. Which might effect to uplift forces. This contribute in difference result between esteem and manual calculation. Last but not least, esteem innovation software can give a better result than manual calculation. Esteem have the accurate result and can make the designing session ease.